Charge selectivity at the lipid-protein interface of membranous Na,K-ATPase. - Brotherus, J R (Proc Natl Acad Sci U S A, 1980)
Lipid interactions with the integral membrane protein Na,K-ATPase (ATP phosphohydrolase, EC 3.6.1.3) purified from the electric organ of Electrophorus electricus were studied by spin labeling. A protein-associated component (boundary layer) in equilibrium with the fluid bilayer is clearly evident in the electron spin resonance spectra. The influence of charge on this equilibrium was determined by varying the head group of the lipid while maintaining the chain length and the position of the label constant. The lipid spin labels were 14-proxylstearylmethyl phosphate and the corresponding dimethylphosphate, alcohol, and quaternary amine. By using a pairwise spectral analysis, as well as a conventional spectral analysis, the binding affinity was found to decrease in the order of negative greater than neutral greater than positive charges. The fraction bound decreased from about 0.57 for the negatively charged phosphate to 0.25 for the positively charged quaternary amine. The amount of each bound lipid was nearly constant over the temperature range investigated (5-35 degrees C). High salt concentrations reversibly abolished the selectivity between the labels, confirming the role of charge in the binding equilibria.